A quantitative genetic examination of non‐target‐site resistance applied to Avena species. (25th January 2018) - Darmency, H; Uludag, A
Summary: Quantitative genetics tools can be used to assess whether using herbicides at low doses drive selection on standing genetic variation in populations leading to non‐target‐site resistance (NTSR). These tools are particularly important for estimating the number of genes involved and the potential speed of evolution. A short cut to answering questions about the evolution of NTSR may be to measure heritability. The heritability index (H) provides a measure of the potential to develop NTSR and can be simply calculated from classical dose–response experiments. This measure and the associated experimental designs are discussed with two applied examples on Avena spp. ( A. fatua and A. sterilis) . In these examples, H values ranged from 0.24 to 0.73, which means that selection for NTSR is highly probable in cases with high H value. We suggest that structuring plants into genetic groups (e.g. families or populations) can contribute to our understanding of the evolutionary potential of populations and plant species to evolve resistance, without increasing experimental cost and time.